ABS filament moisture compensation possibilities in the FDM process. (November 2021) - Wichniarek, Radosław; Hamrol, Adam; Kuczko, Wiesław; Górski, Filip; Rogalewicz, Michał
Highlights: Moist ABS can be processed using the FDM method under specific conditions. Layer thickness is the most important factor interacting with filament humidity. Lower temperatures of the working chamber should be used for moist ABS processing. Abstract: The article presents the possibility of compensating for the negative impact of filament humidity on the mechanical properties of parts produced by the FDM method by selecting appropriate process parameters, such as: layer thickness, deposition speed, deposition temperature and chamber temperature. The rules for selecting the process parameters were established on the basis of the results of the experiment, which allowed to identify the main and internal relations between the properties of the product and the process parameters, as well as the humidity of the filament. It was found, that layer thickness is the parameter of the FDM process which compensates for the negative impact of material moisture to the greatest extent.